Evidence of a Lead Metathesis Product from Calcium Hydroxyapatite Dissolution in Lead Nitrate Solution - Oratai Saisa-ard; Weenawan Somphon; Winya Dungkaew; Kenneth J. Haller (Advances in Materials Science and Engineering)
Calcium hydroxyapatite, CaHAp, synthesized by the precipitation method, was utilized to study the calcium-lead metathesis reaction on dissolution in a lead nitrate solution under reflux conditions to prepare larger lead hydroxyapatite, PbHAp, crystals from CaHAp. SEM images show development of crystalline PbHAp on the surfaces of CaHAp. The needle-like crystal morphology observed for PbHAp after 24 h reaction time developed into hexagonal-rod crystal morphology within 48 h reaction time. The largest PbHAp crystals obtained from 48 h reaction time have approximate size of 10 × 10 × 40 μm. Powder X-ray diffraction results show mixed phases of CaHAp and PbHAp due to difficulty in separating the PbHAp product from the CaHAp substrate. The PbHAp peaks observed after 24 h of reaction sharpen and increase in intensity after 48 h of reaction confirming that the PbHAp phase is the major product for the 48 h reaction time. EDX results of the crystalline products show high intensity Pb peaks with lead to phosphorous ratio (5 : 3) as expected for PbHAp. Lower intensity Ca peaks are also observed, consistent with incomplete coverage of the CaHAp growth substrate.